2018
DOI: 10.1214/17-aos1621
|View full text |Cite
|
Sign up to set email alerts
|

Weak convergence of a pseudo maximum likelihood estimator for the extremal index

Abstract: The extremes of a stationary time series typically occur in clusters. A primary measure for this phenomenon is the extremal index, representing the reciprocal of the expected cluster size. Both a disjoint and a sliding blocks estimator for the extremal index are analyzed in detail. In contrast to many competitors, the estimators only depend on the choice of one parameter sequence. We derive an asymptotic expansion, prove asymptotic normality and show consistency of an estimator for the asymptotic variance. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 27 publications
2
73
0
Order By: Relevance
“…Disjoint blocks yield a larger variance than sliding blocks. Similarly, in [BB18] the authors use the blocking method to estimate the extremal index and again the sliding block estimator is more efficient.…”
Section: Existing Resultsmentioning
confidence: 99%
“…Disjoint blocks yield a larger variance than sliding blocks. Similarly, in [BB18] the authors use the blocking method to estimate the extremal index and again the sliding block estimator is more efficient.…”
Section: Existing Resultsmentioning
confidence: 99%
“…Moreover, the sample of sliding block maxima carries more information than the sample of disjoint block maxima, which suggests the possibility of more accurate inference. Robert et al (2009), Northrop (2015) and Berghaus and Bücher (2016) applied this idea to the estimation of the extremal index, a summary measure for the strength of serial dependence between extremes. They found that estimators based on sliding blocks were indeed more efficient than their counterparts based on disjoint blocks.…”
Section: Introductionmentioning
confidence: 99%
“…to, e.g., denote the disjoint blocks CFG-estimator based on theŶ ni and the sliding blocks madogram-estimator based on theẐ ni , respectively. Note that the four estimators of the formθ yn m,R,1 ,θ zn m,R,1 , m ∈ {db, sb}, are the (pseudo) maximum likelihood (PML) estimators considered in [3].…”
Section: Definition Of the Estimatorsmentioning
confidence: 99%
“…The proposed estimators typically depend on two or, arguably preferable, one parameter to be chosen by the statistician. The present paper is on a class of method of moments estimators (based on the blocks method), which improves upon a recent estimator proposed by Paul Northrop in [22] and analyzed theoretically in [3]. Some notations and assumptions are necessary for the motivation of the new class of estimators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation